Trueperella (Arcanobacterium pyogenes) in Farmed White-Tailed Deer - Samantha M. Wisely; Katherin A. Sayler; Kathryn D. Pothier (EDIS, 2017)
Trueperella is a harmless bacterium in intestinal tracts of ruminants like deer, cattle, and pigs, but if it migrates out of the intestine to other areas of an animal’s body and proliferates, it can make the animal sick. Trueperella causes many problems in deer, including lesions, abscesses, and pneumonia, and it is one of the types of bacteria that is known to contribute to the disease lumpy jaw. In young fawns, it is a common cause of death. This 3-page fact sheet written by Kathryn D. Pothier, Katherine A. Sayler, and Samantha M. Wisely and published by the Department of Wildlife Ecology and Conservation explains how to spot and treat trueperella, or, better yet, prevent it in the first place.http://edis.ifas.ufl.edu/uw427